Dual MRI T sub(1) and T sub(2) super(()) contrast with size-controlled iron oxide nanoparticles - Jung, Hoesu; Park, Bumwoo; Lee, Changkyung; Cho, Junghun; Suh, Jiyeon; Park, JangYeon; Kim, YoungRo; Kim, Jeongkon; Cho, Gyunggoo; Cho, HyungJoon (Nanomedicine, 2014)
Contrast-enhancing magnetic resonance mechanism, employing either positive or negative signal changes, has contrast-specific signal characteristics. Although highly sensitive, negative contrast typically decreases the resolution and spatial specificity of MRI, whereas positive contrast lacks a high contrast-to-noise ratio but offers high spatial accuracy. To overcome these individual limitations, dual-contrast acquisitions were performed using iron oxide nanoparticles and a pair of MRI acquisitions. Specifically, vascular signals in MR angiography were positively enhanced using ultrashort echo (UTE) acquisition, which provided highly resolved vessel structures with increased vessel/tissue contrast. In addition, fast low angle shot (FLASH) acquisition yielded strong negative vessel contrast, resulting in the higher number of discernible vessel branches than those obtained from the UTE method. Taken together, the high sensitivity of the negative contrast delineated ambiguous vessel regions, whereas the positive contrast effectively eliminated the false negative contrast areas (e.g., airways and bones), demonstrating the benefits of the dual-contrast method. From the Clinical Editor In this study, the MRI properties of iron oxide nanoparticles were studied in an animal model. These contrast agents are typically considered negative contrast materials, leading to signal loss on T2* weighted images, but they also have known T1 effects as well, which is lower than that of standard positive contrast agents (like gadolinium or manganese) but is still detectable. This dual property was utilized in this study, demonstrating high sensitivity of the negative contrast in delineating ambiguous vessel regions, whereas the positive contrast eliminated false negative contrast areas (areas giving rise to susceptibility effects).